Effect of preexercise electrolyte ingestion on fluid balance in men and women - Johannsen, N. M.; Lind, E.; King, D. S.; Sharp, R. L. (Medicine & Science in Sports & Exercise, 2009)
Purpose: This article aimed to study the effect of preexercise ingestion of an electrolyte-containing beverage and meal on fluid balance during exercise in men and women.